Morphology and field emission properties of tetrapod shaped Sn doped ZnO nanostructures under different growth times. (November 2015) - Lin, M.; Peng, Y.; Zhou, X.; Lin, T.; Zhang, Y.; Hu, J.; Guo, T.
Abstract : The morphology, microstructure and field emission (FE) properties of tetrapod shaped Sn doped ZnO (T-SZO) nanostructures grown for different times were investigated. It is found that the morphology, particularly the aspect ratio of the T-SZO, can be controlled by adjusting the growth time and that the aspect ratio affects its FE properties. The aspect ratio increases first with the growth time, and after 90 s, a new series of T-SZO with smaller size and lower aspect ratio appear, leading to the deterioration of the FE properties. The sample grown for 90 s exhibits the highest aspect ratio of 16:5 and the lowest turn on field of 1·82 V μm − 1 .